Verification and validation for quality of UML 2.0 models - Unhelkar, Bhuvan (John Wiley, 2005)
This book presents a practical checklist approach to enhancing the quality of software models created with the Unified Modeling Language (UML) Version 2.0. The foundation for quality is set by the discussion on the nature and creation of UML models. This is followed by a demonstration of how to apply verification and validation checks to these models with three foci: syntactical correctness, semantic meaningfulness, and aesthetic symmetry. The quality work is carried out within three distinct yet related modeling spaces: Model of problem space (MOPS); Model of solution space (MOSS); Model of background space (MOBS).